2013
DOI: 10.1016/j.drugalcdep.2013.08.027
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and substance use disorders in adolescence and early adulthood: A prospective analysis

Abstract: Background Dysregulated immune function and elevated inflammation markers are seen in adults with chronic diseases, including some psychiatric disorders, but evidence on inflammation in the case of drug abuse is conflicting. Objective To test the concurrent and predictive relations between C-reactive protein (CRP) and use and abuse of alcohol, nicotine and cannabis in a longitudinal, population sample of adolescents and young adults, at the period of highest increase in drug use. Methods Data from the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 65 publications
5
42
2
3
Order By: Relevance
“…The association between SUD and an increased hsCRP level remained significant in men even after multiple adjustments, which is in line with previous findings regarding increased levels of inflammation markers in alcoholics (Achur et al, 2010) and subjects with cannabis abuse or dependence (Costello et al, 2013). In drinkers, the increased level of pro-inflammatory cytokines has been shown to be associated with chronic and acute alcoholinduced lever diseases, but also with a significant increase in spontaneous cytokine production (Achur et al, 2010).…”
Section: Sud and Inflammationsupporting
confidence: 83%
See 2 more Smart Citations
“…The association between SUD and an increased hsCRP level remained significant in men even after multiple adjustments, which is in line with previous findings regarding increased levels of inflammation markers in alcoholics (Achur et al, 2010) and subjects with cannabis abuse or dependence (Costello et al, 2013). In drinkers, the increased level of pro-inflammatory cytokines has been shown to be associated with chronic and acute alcoholinduced lever diseases, but also with a significant increase in spontaneous cytokine production (Achur et al, 2010).…”
Section: Sud and Inflammationsupporting
confidence: 83%
“…Similarly, chronic exposure to drugs may favor cytokine expression in the brain (Yamada, 2008). Conversely, as suggested by the prospective community study of Costello et al (Costello et al, 2013) a high CRP level is also a predictor of SUD.…”
Section: Sud and Inflammationmentioning
confidence: 84%
See 1 more Smart Citation
“…26,36,51 Tobacco’s effect on periodontal disease is thought to be mediated through increased inflammation and vasoconstriction, 51 which may or may not be the case for cannabis. Cannabis use was not associated with systemic inflammation here or elsewhere, 30,39 but prior research has shown that cannabis can induce vasoconstriction. 52,53 …”
Section: Discussionmentioning
confidence: 72%
“…There has been little epidemiological research on this interesting topic (Costello et al, 2013; Keen et al, 2014; Muniyappa et al, 2013). Due to the large nationally representative sampling and strong CRP assays, of most importance might be recent work based on the United States National Health and Nutrition Examination Survey data gathered between 1988 and 1994 (US NHANES, 1988–1994), completed by Rajavashisth and colleagues (2012).…”
Section: Introductionmentioning
confidence: 99%